WS04.06Observations on CFTR modulators and pancreatic function in a clinical trial of ANG003, a novel pancreatic enzyme replacement therapy in people with cystic fibrosis - Freedman, S.D.; Sathe, M.; Clarkin, M.; Gallotto, D.; Borowitz, D. (Journal of cystic fibrosis, 2025)
Highly efficacious CFTR modulators have greatly improved the daily lives of people with CF. Some patients and providers have attributed improvements in gastrointestinal symptoms to improved pancreatic function. A clinical study in people with cystic fibrosis of ANG003, a novel, microbially-derived lipase, protease and amylase product, required proof of exocrine pancreatic insufficiency as an inclusion criterion but did not have exclusions for concomitant CFTR modulators. We report observations about pancreatic functional status at baseline in this cohort. This multicenter, randomized, parallel, active-treatment study evaluated the safety, tolerability and effect of a single dose of orally administered ANG003 in adult subjects with CF and documented EPI based on fecal elastase (NCT06052293). We enrolled 51 subjects (53% male; 94% white). Mean age was 30 years (range=18-58). On study entry, subjects were taking ∼5 capsules of porcine pancreatic enzyme replacement therapy per meal and 3 per snack (mean=20 capsules/day (range: 6-43 capsules); mean lipase units per day 548,000 (168,000-1,080,000); mean 8,000 lipase units/kg/day; 22% of subjects were taking >10,000 units/kg/day). CFTR modulators were being taken by 47 subjects (92%). All were taking elexacaftor/ tezacaftor/ivacaftor with the exception of two subjects taking ivacaftor alone. Subjects had been taking these modulators for a median of 3.7 years (range 1 month-6.6 years). Fecal elastase values were all in the range consistent with severe pancreatic insufficiency. The median value was <40 ug/g. These data add to the body of information that adults taking highly efficacious CFTR modulators are not associated with objective improvement in pancreatic function. In addition, we observed lack of conformity with guidelines on limits of pancreatic enzyme dose per day.